Peran Guru Bimbingan dan Konseling dalam Membina Kedisiplinan Belajar Siswa - Sudiansyah, Sudiansyah; Lutfi, Mutia; Bosco, Fabianus Hadiman; Putra, Rahman Pranovri; Fauziyah, Wiwin Rif'atul; Rais, Rinovian; Haddar, Gamar Al (Global Education Journal, 2023)
Building student learning discipline is a process that needs to be done gradually and continuously. Students need to have a consistent study schedule every day. This study aims to determine the role of guidance and counseling teachers in fostering learning discipline in class XII-B students Ma Ma'arif Al-Ishlah Kalisat Bungkal Ponorogo. The research method used is a qualitative approach, a type of phenomenology. Data collection techniques with observation, interviews and documentation. Data were analyzed by phenomenological analysis with the stages given by Miles and Huberman, namely data condensation, data presentation and conclusions. Data validity uses source triangulation. The results of this study state that guidance and counseling teachers play a significant role in student learning discipline.